Myofunctional therapy (oropharyngeal exercises) for obstructive sleep apnoea - Rueda, José-Ramón; Mugueta-Aguinaga, Iranzu; Vilaró, Jordi; Rueda-Etxebarria, Mikel (Cochrane database of systematic reviews, 2020)
Obstructive sleep apnoea (OSA) is a syndrome characterised by episodes of apnoea (complete cessation of breathing) or hypopnoea (insufficient breathing) during sleep. Classical symptoms of the disease - such as snoring, unsatisfactory rest and daytime sleepiness - are experienced mainly by men; women report more unspecific symptoms such as low energy or fatigue, tiredness, initial insomnia and morning headaches. OSA is associated with an increased risk of occupational injuries, metabolic diseases, cardiovascular diseases, mortality, and being involved in traffic accidents. Continuous positive airway pressure (CPAP) - delivered by a machine which uses a hose and mask or nosepiece to deliver constant and steady air pressure- is considered the first treatment option for most people with OSA. However, adherence to treatment is often suboptimal. Myofunctional therapy could be an alternative for many patients. Myofunctional therapy consists of combinations of oropharyngeal exercises - i.e. mouth and throat exercises. These combinations typically include both isotonic and isometric exercises involving several muscles and areas of the mouth, pharynx and upper respiratory tract, to work on functions such as speaking, breathing, blowing, sucking, chewing and swallowing. To evaluate the benefits and harms of myofunctional therapy (oropharyngeal exercises) for the treatment of obstructive sleep apnoea. We identified randomised controlled trials (RCTs) from the Cochrane Airways Trials Register (date of last search 1 May 2020). We found other trials at web-based clinical trials registers. We included RCTs that recruited adults and children with a diagnosis of OSA. We used standard methodological procedures expected by Cochrane. We assessed our confidence in the evidence by using GRADE recommendations. Primary outcomes were daytime sleepiness, morbidity and mortality. We found nine studies eligible for inclusion in this review and nine ongoing studies. The nine included RCTs analysed a total of 347 participants, 69 of them women and 13 children. The adults' mean ages ranged from 46 to 51, daytime sleepiness scores from eight to 14, and severity of the condition from mild to severe OSA. The studies' duration ranged from two to four months. None of the studies assessed accidents, cardiovascular diseases or mortality outcomes. We sought data about adverse events, but none of the included studies reported these. In adults, compared to sham therapy, myofunctional therapy: probably reduces daytime sleepiness (Epworth Sleepiness Scale (ESS), MD (mean difference) -4.52 points, 95% Confidence Interval (CI) -6.67 to -2.36; two studies, 82 participants; moderate-certainty evidence); may increase sleep quality (MD -3.90 points, 95% CI -6.31 to -1.49; one study, 31 participants; low-certainty evidence); may result in a large reduction in Apnoea-Hypopnoea Index (AHI, MD -13.20 points, 95% CI -18.48 to -7.93; two studies, 82 participants; low-certainty evidence); may have little to no effect in reduction of snoring frequency but the evidence is very uncertain (Standardised Mean Difference (SMD) -0.53 points, 95% CI -1.03 to -0.03; two studies, 67 participants; very low-certainty evidence); and probably reduces subjective snoring intensity slightly (MD -1.9 points, 95% CI -3.69 to -0.11 one study, 51 participants; moderate-certainty evidence). Compared to waiting list, myofunctional therapy may: reduce daytime sleepiness (ESS, change from baseline MD -3.00 points, 95% CI -5.47 to -0.53; one study, 25 participants; low-certainty evidence); result in little to no difference in sleep quality (MD -0.70 points, 95% CI -2.01 to 0.61; one study, 25 participants; low-certainty evidence); and reduce AHI (MD -6.20 points, 95% CI -11.94 to -0.46; one study, 25 participants; low-certainty evidence). Compared to CPAP, myofunctional therapy may result in little to no difference in daytime sleepiness (MD 0.30 points, 95% CI -1.65 to 2.25; one study, 54 participants; low-certainty evidence); and may increase AHI (MD 9.60 points, 95% CI 2.46 to 16.74; one study, 54 participants; low-certainty evidence). Compared to CPAP plus myofunctional therapy, myofunctional therapy alone may result in little to no difference in daytime sleepiness (MD 0.20 points, 95% CI -2.56 to 2.96; one study, 49 participants; low-certainty evidence) and may increase AHI (MD 10.50 points, 95% CI 3.43 to 17.57; one study, 49 participants; low-certainty evidence). Compared to respiratory exercises plus nasal dilator strip, myofunctional therapy may result in little to no difference in daytime sleepiness (MD 0.20 points, 95% CI -2.46 to 2.86; one study, 58 participants; low-certainty evidence); probably increases sleep quality slightly (-1.94 points, 95% CI -3.17 to -0.72; two studies, 97 participants; moderate-certainty evidence); and may result in little to no difference in AHI (MD -3.80 points, 95% CI -9.05 to 1.45; one study, 58 participants; low-certainty evidence). Compared to standard medical treatment, myofunctional therapy may reduce daytime sleepiness (MD -6.40 points, 95% CI -9.82 to -2.98; one study, 26 participants; low-certainty evidence) and may increase sleep quality (MD -3.10 points, 95% CI -5.12 to -1.08; one study, 26 participants; low-certainty evidence). In children, compared to nasal washing alone, myofunctional therapy and nasal washing may result in little to no difference in AHI (MD 3.00, 95% CI -0.26 to 6.26; one study, 13 participants; low-certainty evidence). Compared to sham therapy, myofunctional therapy probably reduces daytime sleepiness and may increase sleep quality in the short term. The certainty of the evidence for all comparisons ranges from moderate to very low, mainly due to lack of blinding of the assessors of subjective outcomes, incomplete outcome data and imprecision. More studies are needed. In future studies, outcome assessors should be blinded. New trials should recruit more participants, including more women and children, and have longer treatment and follow-up periods.